Captain America, Masculinity, and Violence : The Evolution of a National Icon - Stevens, J. Richard (Book collections on Project MUSE., 2015)
"Captain America's adventures span from World War II through the Cold War to the American War on Terror. In Captain America, Masculinity, and Violence, Stevens reveals how the hero evolved to maintain relevance to America's fluctuating ideas of masculinity, patriotism, and violence. Tracking the history of Captain America's adventures, Stevens places them in dialogue with the comic book industry as well as American politics, showing how the hero represents the ultimate American story: permanent enough to survive for more than seventy years with a history fluid enough to be constantly reinterpreted to meet the needs of an ever-changing culture, "--Back cover